2013
DOI: 10.1021/tx300499c
|View full text |Cite
|
Sign up to set email alerts
|

Reaction between Peroxynitrite and Triphenylphosphonium-Substituted Arylboronic Acid Isomers: Identification of Diagnostic Marker Products and Biological Implications

Abstract: Aromatic boronic acids react rapidly with peroxynitrite (ONOO−) to yield phenols as major products. This reaction was used to monitor ONOO− formation in cellular systems. Previously, we proposed that the reaction between ONOO− and arylboronates (PhB(OH)2) yields a phenolic product (major pathway) and a radical pair PhB(OH)2O•−…•NO2 (minor pathway). [Sikora A. et al., Chem Res Toxicol 24, 687-97, 2011]. In this study, we investigated the influence of a bulky triphenylphosphonium (TPP) group on the reaction betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
61
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 43 publications
5
61
0
Order By: Relevance
“…11). We have shown previously that stimulation of RAW 264.7 cells leads to formation of o-MitoPhOH and small amounts of o-MitoPhNO 2 (21,22). As shown in Fig.…”
Section: Inhibition Of Nox2 In Activated Raw 2647 Macrophages-mentioning
confidence: 59%
See 2 more Smart Citations
“…11). We have shown previously that stimulation of RAW 264.7 cells leads to formation of o-MitoPhOH and small amounts of o-MitoPhNO 2 (21,22). As shown in Fig.…”
Section: Inhibition Of Nox2 In Activated Raw 2647 Macrophages-mentioning
confidence: 59%
“…8a) and is unaffected by glutathione or other biologically relevant reductants (21,22). As this product is not fluorescent, we used HPLC with absorption detection for quantitative analyses, and we confirmed it is formed in RAW 264.7 cells in activated macrophages (22). However, using an LC-MS/MS method, we found that this product (i.e.…”
Section: Inhibition Of Nox2 In Activated Raw 2647 Macrophages-mentioning
confidence: 72%
See 1 more Smart Citation
“…This is, in part, due to the lack of availability of specific probes that directly react with ONOO Ϫ to form specific diagnostic products. Here, we present unambiguous evidence for ONOO Ϫ formation during the reaction between HNO and molecular oxygen using the recently developed assays for specific detection and quantification of peroxynitrite (47,48).…”
mentioning
confidence: 94%
“…More precisely, it reacts with the conjugate base of hydrogen peroxide, the hydroperoxide anion, so that the higher pH of the mitochondrial matrix gives an additional four---fold acceleration relative to reaction in the cytosol. With the exception of peroxynitrite and HOCl, other ROS do not react with MitoB to give this product (51,52). Importantly, the rate constant for reaction between the mitochondrial peroxidase, peroxiredoxin III, and hydrogen peroxide is over a million times higher than that for reaction with MitoB (49).…”
Section: Mitochondria---targeted Sensorsmentioning
confidence: 99%